Conceptual Systems Theory: A Neglected Perspective for the Anthropology of Consciousness. (March 2017) - Laughlin, Charles D.
Abstract: As anthropology becomes more interested in consciousness and its numerous states, and with a slowly increasing appeal to neuroscience for insights and explanations of consciousness, there is an understandable interest in the components of consciousness and how they combine into alternative states in different sociocultural settings. One of those components should be the complexity of information processing producing the knowing aspect of consciousness. The author introduces an approach to this aspect in the form of conceptual systems theory (CST), a neo‐Piagetian model of cognitive development, which has been used to good effect to explain information processing in social situations but heretofore neglected by anthropologists. The neuroanthropological underpinnings of CST are discussed, as is the range of potential applications to ethnological and ethnographic problems.